Bioequivalence of Saxagliptin/Metformin Extended-Release (XR) Fixed-Dose Combination Tablets and Single-Component Saxagliptin and Metformin XR Tablets in Healthy Adult Subjects - Boulton, David W.; Smith, Charles H.; Li, L.; Huang, Jian; Tang, Angela; LaCreta, Frank P. (Clinical drug investigation, 2011)
Background and Objectives: As compared with individual tablets, saxagliptin/metformin extended-release (XR) fixed-dose combination (FDC) tablets offer potential for increased patient compliance with the convenience of once-daily dosing. Two bioequivalence studies assessed the fed-state bioequivalence of saxagliptin/metformin XR 5 mg/500 mg FDC (study 1) and saxagliptin/metformin XR 5mg/1000 mg FDC (study 2) relative to the same dosage strengths of individual component tablets administered concurrently. The effect of food on saxagliptin and metformin pharmacokinetics from the saxagliptin/metformin XR 5 mg/500 mg FDC and their steady-state pharmacokinetics from the saxagliptin/metformin XR 5 mg/1000 mg were also investigated. Methods: These were randomized, open-label, single-dose, three-period, three-treatment, crossover studies in healthy subjects (n=30 in each study). The treatments in study 1 were a saxagliptin/metformin XR 5 mg/500 mg FDC tablet in the fed and fasted states on separate occasions, and saxagliptin 5 mg and metformin XR 500 mg co-administered in the fed state. The treatments in study 2 were a saxagliptin/metformin XR 5 mg/1000 mg FDC tablet in the fed state, saxagliptin 5 mg and 2 × metformin XR 500 mg co-administered in the fed state, and saxagliptin/metformin XR 5 mg/1000 mg FDC once daily for 4 days in the fed state to assess steady-state pharmacokinetics. The safety and tolerability of each treatment were also evaluated. Results: For both studies, saxagliptin and metformin in the FDCs were bio-equivalent to the individual components as the limits of the 90% confidence interval of the ratio of adjusted geometric means for all key pharmacokinetic parameters were contained within 0.800 to 1.250. Compared with the fasted state, food did not have a meaningful effect on the pharmacokinetics of saxagliptin and metformin when administered as the saxagliptin/metformin XR 5 mg/500 mg FDC. The saxagliptin/metformin XR 5 mg/1000 mg FDC showed consistent pharmacokinetics at steady state without evidence of dose dumping. Co-administration of saxagliptin and metformin XR was generally safe and well tolerated as the FDCs or as individual tablets. Conclusion: Saxagliptin/metformin XR 5 mg/500 mg and saxagliptin/metformin XR 5 mg/1000 mg FDCs were bioequivalent to individual tablets of saxagliptin and metformin of the same strengths. Additionally, food had little effect on the pharmacokinetics of saxagliptin and metformin administered in the saxagliptin/metformin XR 5 mg/500 mg FDC and the steady-state pharmacokinetics of the saxagliptin/metformin XR 5 mg/1000 mg FDC was consistent over time. No unexpected safety findings were observed with saxagliptin/metformin XR administration. The tolerability of the FDC of saxagliptin/metformin XR was comparable to that of the co-administered individual components. These results indicate that the safety and efficacy profile of co-administration of saxagliptin and metformin can be extended to the saxagliptin/metformin XR FDC tablets. Trials Registration: ClinicalTrials.gov Identifiers: NCT01192139 and NCT01192152.